2008
DOI: 10.1177/1403494807085307
|View full text |Cite
|
Sign up to set email alerts
|

Associations between strain in domestic work and self-rated health: A study of employed women in Sweden

Abstract: Strain in domestic work, including perceived inequity in the relationship and lack of a satisfactory relationship with a spouse/cohabiter, was associated with lower self-rated health in this cross-sectional study. Future research needs to address the specific importance of strain in domestic work as a contributory factor to women's ill-health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 23 publications
6
53
1
2
Order By: Relevance
“…In analogy with the concept of job strain, an instrument called 'domestic strain' was recently developed. This measure, as well as 'perceived inequity in the relationship with spouse/cohabiter', was associated with lower self-rated health (Staland-Nyman, Alexanderson, & Hensing, 2008). In the future, the domain of household work should be further explored both from a methodological and an empirical point of view.…”
Section: Methodological Considerations and Comparison With Previous Smentioning
confidence: 98%
“…In analogy with the concept of job strain, an instrument called 'domestic strain' was recently developed. This measure, as well as 'perceived inequity in the relationship with spouse/cohabiter', was associated with lower self-rated health (Staland-Nyman, Alexanderson, & Hensing, 2008). In the future, the domain of household work should be further explored both from a methodological and an empirical point of view.…”
Section: Methodological Considerations and Comparison With Previous Smentioning
confidence: 98%
“…Östlund et al (2004) have identified three dimensions of domestic strain that influence sickness absence: the division of domestic work, the division of responsibility for domestic life and the amount of social-emotional support at home. Staland-Nyman et al (2007) have found correlations between domestic work strain, domestic work equity, marital satisfaction and self-related health.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Östlund et al (2004) and Staland-Nyman et al (2007) emphasize the importance of using measures that also include emotional content of domestic work. Our study illustrates that a sufficient understanding of the factors contributing to sick leave requires the inclusion of emotional dimensions in both the workplace and the domestic sphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations